2023
DOI: 10.3390/ma16093426
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Synthesis Parameters Effects on the Structural, Morphological, and Magnetic Properties of Copper Oxide Nanoparticles

Abstract: The present study aims at the integration of the “oxalic conversion” route into “green chemistry” for the synthesis of copper oxide nanoparticles (CuO-NPs) with controllable structural, morphological, and magnetic properties. Two oxalate-containing precursors (H2C2O4.2H2O and (NH4)2C2O4.H2O) and different volume ratios of a mixed water/glycerol solvent were tested. First, the copper oxalates were synthesized and then subjected to thermal decomposition in air at 400 °C to produce the CuO powders. The purity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…When comparing the particle sizes (D) obtained from TEM or SEM with the crystallite sizes (D XRD ) calculated using the Scherrer equation, it is observed that the D XRD values are smaller than those of D. This suggests that most of the synthesized nanoparticles consist of a crystalline multidomain structure. These results are consistent with findings in the literature, which generally indicate that particle sizes estimated using the Scherrer equation are smaller than the real sizes observed in TEM or SEM micrographs 49,50 . These discrepancies between D XRD and D values may be attributed to factors such as nanoparticle aggregation, the presence of large particles, and the polydispersity of particle sizes 46,51 .…”
Section: Resultssupporting
confidence: 92%
“…When comparing the particle sizes (D) obtained from TEM or SEM with the crystallite sizes (D XRD ) calculated using the Scherrer equation, it is observed that the D XRD values are smaller than those of D. This suggests that most of the synthesized nanoparticles consist of a crystalline multidomain structure. These results are consistent with findings in the literature, which generally indicate that particle sizes estimated using the Scherrer equation are smaller than the real sizes observed in TEM or SEM micrographs 49,50 . These discrepancies between D XRD and D values may be attributed to factors such as nanoparticle aggregation, the presence of large particles, and the polydispersity of particle sizes 46,51 .…”
Section: Resultssupporting
confidence: 92%
“…Also, recently, Cu-Ag NPs with tunable compositions and structures have been synthesized using femtosecond laser reduction in solutions of copper and silver precursor [34]. Magnetic properties of copper oxide NPs have been also reported which can be used in Ag-Cu NPs to provide the magnetic properties in the NPs [35]. Silver-copper thin films with an average diameter of NPs ∼4 nm have been deposited by DC magnetic sputtering under nitrogen gas at different deposition times and their results showed that surface plasmon resonance (SPR) wavelength of the deposited thin film experienced a sharply blue shift by increasing the deposition time from 8 to 24 min [36].…”
Section: Introductionmentioning
confidence: 99%